Vermicompost extract as a basal medium in the in vitro multiplication and rooting stage of Dasylirion cedrosanum - Ramírez-Gottfried , Ricardo Israel; Puente-Valenzuela , Cristo Omar; Chávez-Simental, Jorge Armando; Espinosa-Palomeque, Bernardo; García-Carrillo, Mario; Guillén-Enríquez, Reyna Roxana; González-Cervantes, Guillermo (REVISTA TERRA LATINOAMERICANA, 2021)
Dasylirion cedrosanum is a native species of the Chihuahuan Desert that is economically important for alcohol production, which has caused its looting and deforestation. In the micropropagation technique, the Murashige and Skoog (MS) basal medium is the most widely used, this basal medium increases costs at the commercial level. The objective of this work was to compare the MS medium with an organic basal medium made from a vermicompost extract (EV) in the multiplication and rooting stages of D. cedrosanum. Seeds were established in MS medium for germination. Then, the seedlings obtained were used as secondary explants for the multiplication stage. In the multiplication stage, seven treatments were evaluated under a completely randomized design with 10 replications. A control (MS medium) and six EV concentrations (30, 25, 20, 15, 10 and 5 mL L-1) were compared. Our results showed the highest sprout formation in the control treatment (8.25 sprouts per explant). Whereas in the EV base treatments, the 25 ml L‑1 concentration exhibited the highest number of sprouts (3 sprouts per explant). It is worth noting that no significant differences were found between the control and the 25 ml L-1 concentration treatments in terms of the number of variables and leaf length. In the rooting stage, there was no significant difference between treatments in the root number. The MS medium and 10 ml L-1 of EV was not statistically different according to root length (6.53 and 5.99 cm, respectively), the 10 ml L-1 concentration of EV surpassed the MS in root width (1.13 mm). The EV based medium at a concentration of 10 ml L-1 can be used to completely to replace the MS medium in the rooting stage of D. cedrosanum.